KOMITMEN MANAJER DALAM PELAKSANAAN KESELAMATAN DAN KESEHATAN KERJA DI RUMAH SAKIT UMUM PUSAT DR. SARDJITO YOGYAKARTA - , AGUS DARMAWAN, Prof. Dr. dr. Adi Heru Sutomo, M.Sc., D.Comm.Nutr., DLSHTM., PKK ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Hospitals facilities has a risk to develop accidents to patients, employees and visitors of the hospital. Occupational Health and Safety (OHS) must be implemented in all workplaces where there are employees are at risks. Dr. Sardjito Hospital is a Class A hospital that has hosted OHS. The management of hospital must be committed in the execution of OHS inside Dr. Sardjito Hospital. Methods: This is a qualitative research with case study design. The subject of this research is Research and Education and Human Resource Director, Head of Occupational Health and Safety Unit, Head of Sub Division in Unit Occupational Health and Safety and workers who have and have not received training in the Hospital of Dr. Sardjito. This Research instrument using an interview guide to conduct in-depth interviews and sheet check list to conduct the survey. Results: Dr. Sardjito Hospital has implemented safety and health since 1995 and continues to grow until now had been own a Unit of Occupational Health and Safety in the hospital. Overall the implementation of occupational safety and health has been good in the department of Dr. Sardjito. However, the support of aspects of budgeting is not maximal. Commitments of management related budgeting already exist, but have not maximal. It seems because of not all of the work program planning carried out because of constrained in funding. Commitment to the implementation of occupational health and safety policy aspects indicated by the policy and activelly participate in the implementation and monitoring of policy. Commitment of infrastructure aspects indicated by the availability of human resources and facilities such as work space, and equipment to support the operational of implementation. Conclusion: The manager commitment related to the Dr. Sardjito Hospital in the implementation of Occupational Health and safety as a whole are shown through policies and supporting facilities and infrastructure in the implementation of safety and health. However, the support of aspects of budgeting is not maximized.